Tracking changes the learning spaces of selected academic libraries in Metro Manila - Dela Torre, Aisa M. (2015)
This study was conducted to determine the extent to which Metro Manila academic libraries adhered to the philosophy and design of learning spaces. It is also an inventory of learning spaces of selected Metro Manila academic libraries in the past ten (10) years from 2005-2014.